Administrative Administration And Social-Political Situation Of The Cities Of Kashkadarya And Surkhandarya Oases During Bukhara Emirate (Eurasian Journal of History, Geography and Economics, 2025)
The article analyzes the administrative-territorial structure of the cities of the Kashkadarya (Kitab, Shakhrisabz, Karshi, Guzar, Yakkabag) and Surkhandarya (Sherabad, Boysun, Denov) oases within the Bukhara Emirate in the 19th century, the management system, and the functions of the officials who worked in them. It also covers the socio-political life of these cities, the causes and consequences of the population's protests against the emir and the popular uprisings